Economic outlook for Southeast Asia, China and India 2018 fostering growth through digitalisation. (OECD Publishing, 2018)
"The Economic Outlook for Southeast Asia, China and India is a bi-annual publication on regional economic growth, development and regional integration in Emerging Asia. It focuses on the economic conditions of Association of Southeast Asian Nations (ASEAN) member countries: Brunei Darussalam, Cambodia, Indonesia, Lao PDR, Malaysia, Myanmar, the Philippines, Singapore, Thailand and Viet Nam. It also addresses relevant economic issues in China and India to fully reflect economic developments in the region. Each edition of the Outlook comprises four main parts, each highlighting a particular dimension of recent economic developments in the region. The first part presents the regional economic monitor, depicting the economic outlook and macroeconomic challenges in the region. The second part takes stock of recent progress made in key aspects of regional integration. The third part consists of a special thematic chapter addressing a major issue facing the region. The 2018 edition focuses on fostering growth through digitalisation. And the fourth part includes structural policy country notes offering country-specific reviews and recommendations."--Provided by publisher.